Study of Intermolecular Interaction by Ultrasonic Measurements of 1-Butanol-Pyridine and Toluene-Pyridine at 303.15 To 323.15 K and Statistical Analysis of Liquid State Theories (International Journal of Scientific Research in Science and Technology, 2024)
The experimental parameters measured in binary liquid mixtures, such as ultrasonic velocity (u) and density (ρ) containing 1-butanol-pyridine and toluene-pyridine across the full range of composition at different temperatures 303.15K to 323.15K, are used to evaluate acoustical parameters. The parameters are also theoretically calculated by using the Jacobson free length theory (flt) and Kalidoss revised free length theory (rflt). The statistical analysis of the liquid state theories has been done by applying chi-square (χ2) test. The findings were explained in terms of the liquid state theories that applied to binary liquid mixes as well as molecular interaction.